INNOVATION OF MEDICINE PLANTS PROPAGATION WITH VERTICULTURE TECHNIQUES IN EFFORTS TO OVERCOME LAND DYSFUNCTIONAL IN EAST SURABAYA AREA - Junairiah Junairiah; Tri Nurhariyati; Listijani Suhargo (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Keputih Village is located in eastern Surabaya. The boundary of this village is the river. Areas on the river banks are overgrown with wild plants and poorly maintained. One way to overcome the dysfunctional land around the river is by cultivating medicinal plants with verticulture techniques. Purpose: The implementation of this program is to overcome the dysfunctional land around the Keputih Village’s river by cultivating medicinal plants in verticulture techniques and provide training in the manufacture of herbal products from the cultivation of medicinal plants and provide financial management training to the local residents. Methods: This activity was carried out in 4 stages. Phase I was training in making pots and verticulture shelves as well as planting medicinal plants, Phase II was mentoring in the field, Phase III was training on making herbal products from plants and training on simple bookkeeping, Phase IV was product display. Results: Based on the results of this training showed that the knowledge of the participants related to the training material has increased which shown from the results of the posttest with average of 79,31 and product display. Conclusion: In this activity, beside gaining knowledge, participants can apply this knowledge to increase family income.